Mammography use for breast cancer screening in Portugal: results from the 2005/2006 National Health Survey - Dourado, F (2013)
Background: Understanding the patterns of mammography use is essential to promote the participation in breast cancer screening. Objectives: To describe the patterns of screening mammography use in Portugal. Methods: As part of the fourth National Health Survey (2005/2006), 3045 women were evaluated in face-to-face interviews. The previous use of mammography for screening was classified as never or ever, and the latter was further grouped according to the time elapsed since the latest mammography. Having undergone the latest mammography >2 years before was considered underuse. We assessed the determinants of never having been screened by mammography and, among those who had been tested, the determinants of mammography underuse, through age- and education-adjusted odds ratios (ORs), with 95% confidence intervals (95% CIs). Results: Among women aged 45–49 and 50–69 years, 86.3% and 88.0%, respectively, underwent a screening mammography before, and most of them were tested in the previous 2 years. The lowest risk of never having been screened was in Norte (OR = 0.41, 95% CI: 0.21–0.80) and the highest in Açores (OR = 4.04, 95% CI: 2.37–6.92), in comparison with Centro (the region with organized screening for a longer time). Participants with <4 years of formal education were more likely to have never been screened than the more educated (OR = 4.27, 95% CI: 1.67–10.89). Women with private health insurance (OR = 0.16, 95% CI: 0.04–0.65), as well as those who had undergone cervical cytology screening before (OR = 0.50, 95% CI: 0.30–0.85), had a lower risk of underuse. Conclusions: This study provides useful information to improve the allocation of resources to breast cancer screening.